2009
DOI: 10.1108/17515630910956570
|View full text |Cite
|
Sign up to set email alerts
|

Business incubation as strategy

Abstract: PurposeThe purpose of this paper is to propose that an unprecedented revolutionary change in the structure of the US economy warrants attention to the internal structures, cultures and strategies. Consequently, it is argued that for businesses, especially large industrial establishments (LIEs), to survive and prosper in the new and emerging economic order, they must aggressively redesign their organizational environments as a business incubator to leverage new and emerging social and economic opportunities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Second, most studies in the above literature relate to the performance of incubators in developed countries and very less in developing countries [21]. Eshun [22] has suggested that government efforts should also be incorporated to assess the business incubator's performance.…”
Section: Role Of Business Incubators In Entrepreneurship Developmentmentioning
confidence: 99%
“…Second, most studies in the above literature relate to the performance of incubators in developed countries and very less in developing countries [21]. Eshun [22] has suggested that government efforts should also be incorporated to assess the business incubator's performance.…”
Section: Role Of Business Incubators In Entrepreneurship Developmentmentioning
confidence: 99%
“…Eshun () and Aernoudt () argue for different types of incubators, as illustrated in Table , while Carayannis and von Zedwitz (, p. 95) present five incubator archetypes: the university incubator, the independent commercial incubator, the regional business incubator, the company‐internal incubator and the virtual incubator. Deriving from the Carayannis and von Zedwitz's () definitions, the fundamental differences between different incubator models/types stem from (1) the purpose of the incubator and (2) the nature of relationships it manages.…”
Section: Linking Incubation and Social Innovationmentioning
confidence: 99%
“…Incubators are designed to provide a variety of resources that will increase the odds that a new business will succeed, and in that success, there will be some economic benefits derived from the sponsoring entity [26]. Moreover, a business incubator has been defined as "an environment formally designed to stimulate the growth and development of new and early stage firms by improving their opportunities for the acquisition of resources aimed at facilitating the development and commercialization of new products, new technologies, and new business models" [27]. It is also defined by [25] as a facility founded to create a conducive environment to new ventures to help them to cope with the difficulties that exist in the initial stage of the business life cycle, to help them to survive and grow to become successful mature businesses.…”
Section: A Incubators: History and Definitionsmentioning
confidence: 99%